PENGARUH PENGGUNAAN MEDIA FLASH CARD (KARTU GAMBAR) DALAM MENINGKATKAN KEMAMPUAN MEMBACA ANAK PRASEKOLAH DI TK B SEGUNUNG MOJOKERTO - Rahmawati, Ima (JURNAL KEPERAWATAN BINA SEHAT, 2013)
This learning is anattempt to determine the influence of learning to use the media to play a flash card(card image) to the reading ability of preschool children. The purpose of this study was to determine the effect of flash card(card image) to the reading ability of preschool children in kindergarten Segunung of Mojokerto. This study used an experimental method to approach one group pre-post test.The population is all students Kindergarten B, amounting to 35 children. The samples are 25 children who meet the inclusion and exclusion criteria with purposive sampling. Media Flash card independent variable (card image) and the dependent variable of reading ability..Reading ability in this study was measured using prosentase. Taking outcome data using observation and treatment.Analysis is used to find the effect of flash cards toi mprove reading skills of preschool children is the Wilcoxon test.Statistical results show the value ofp=0.000(p <0.05) withZ=-4304 means that there is the effect of play therapy flash cards (card images). Based on the analysisit can be concluded that the use flash card learning (card images) is effective in improving reading skills preschool children in kindergarten B Segunung of Mojokerto.Flash card consists of some sort, such as of the alphabet flash card, flash card math, reading flash cards, flash card history and social, science flash card, flash cards hijaiyah.Keywords: flash card, Literacy, Preschool